2013
DOI: 10.1089/ten.tec.2012.0126
|View full text |Cite
|
Sign up to set email alerts
|

The Adjuvant Use of Stromal Vascular Fraction and Platelet-Rich Fibrin for Autologous Adipose Tissue Transplantation

Abstract: Autologous adipose transplantation is rapidly gaining popularity for the restoration of soft tissue defects and lipoatrophy as well as for aesthetic improvements (e.g., facial reconstruction and rejuvenation). However, the current technique is crude that suffers from serious demerits, particularly the long-term unpredictability of volume maintenance due to resorption of the grafted adipose tissue and limited adipogenesis. We hypothesized that the adjuvant use of patient-derived adipose stromal vascular fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 58 publications
0
49
1
3
Order By: Relevance
“…Several studies confirmed the gradual release of PDGF and TGF for 28 days from PRF, comparing the burst release of PRP within 1 day. 50,51 A possible explanation is that PRF polymerizes with 3D architecture progressively, slowly, and naturally during centrifugation, which helps to entrap cytokines released from platelets with the fibrin polymer. In contrast, PRP is activated with a high concentration of thrombin, which makes the polymerization rapid, followed by strong contraction of the clots, from which fluids will expel.…”
Section: Platelet-rich Fibrin and Its Effect On Fat Graftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies confirmed the gradual release of PDGF and TGF for 28 days from PRF, comparing the burst release of PRP within 1 day. 50,51 A possible explanation is that PRF polymerizes with 3D architecture progressively, slowly, and naturally during centrifugation, which helps to entrap cytokines released from platelets with the fibrin polymer. In contrast, PRP is activated with a high concentration of thrombin, which makes the polymerization rapid, followed by strong contraction of the clots, from which fluids will expel.…”
Section: Platelet-rich Fibrin and Its Effect On Fat Graftsmentioning
confidence: 99%
“…Liu et al studied the effect of autologous PRF and/or SVF on fat graft survival. 50 They implanted a mixture of fat graft with PRF alone, SVF alone, or PRF with SVF on the rabbit ear. After 4 weeks, there was higher microvessel density and remaining adipose tissue area in the PRF + SVF + fat graft group compared to the other groups.…”
Section: Platelet-rich Fibrin and Its Effect On Fat Graftsmentioning
confidence: 99%
“…cells. Thus, the efficacy of linpopulation might be correlated with its use in specific treatment of mesodermal related disorders such as bone and cartilage dysfunctions, soft tissue augmentation, muscular disorders and so on (Vieira et al 2008;Liu et al 2012;Lendeckel et al 2004). On the other hand, the efficacy of lin?…”
Section: Discussionmentioning
confidence: 99%
“…3. Результаты экспериментальных исследований использования СВКФ и плазмы, обогащенной факторами роста, для приживления жировой ткани: 1) гистологическая картина; 2) визуальная оценка на кроликах [28]. Fig.…”
Section: выделение и применение ск жировой ткани в пластической хирургииunclassified